Laminated connections for structural glass applications under shear loading at different temperatures and strain rates. (15th December 2016) - Santarsiero, Manuel; Louter, Christian; Nussbaumer, Alain
Graphical abstract: Highlights: Experimental investigation of novel laminated connections with transparent adhesives under shear loading. Quantitative evaluation of temperature and strain rate effects. Non-linear finite element analysis for the computation of the three-dimensional stress field distribution. Validation with experimental tests. Probabilistic development of failure prediction model. Abstract: Connections between structural glass components represent one of the main critical aspects of glass engineering. In the last years, a novel typology of adhesive connections has emerged, known as laminated adhesive connections. Two adhesive materials for laminated connections in glass applications are used in this work: the transparent ionomer SentryGlas® (SG) from Kuraray and the Transparent Structural Silicon Adhesive (TSSA) from Dow Corning. Both SG and TSSA show a complex behaviour dependent on strain rate and temperature. This work presents a study that aims (i) to investigate the mechanical behaviour and strength of this connection typology under shear loading and (ii) to quantify the effects of strain rate and temperature on the strength of the connections. This is done by means of a combined experimental, analytical and numerical study on laminated connections made of circular metal connectors bonded to rectangular glass plates. The experimental investigations presented in this work showed that temperature and strain rate variations have important effects on the mechanical response of the connections. Three-dimensional numerical analyses showed a non-uniform stress field with large gradient over the three dimensions. Through analytical studies, prediction models are finally proposed for the shear resistance of TSSA and SG laminated connections. The models are obtained developing an algorithm for multi-dimensional non-linear models with variable standard deviations. A logarithmic law is proposed for the strain rate effects for both TSSA and SG connections. Linear and inverse hyperbolic-tangent-based laws are instead proposed for the TSSA and SG temperature behaviour respectively.